Reconstruction of The Policy License for Tourism Businesses: Challenge and Opportunity for Social Welfare - Eny Suastuti; Hayyan ul Haq; George Muishot; Tatiek Sri Djamiati; Firman Arif (BESTUUR, 2024)
The government's policy of revoking the authority of local governments to issue permits for the tourism business sector has caused chaos in the management and supervision of tourism businesses. This takeover of authority is closely related to the business licensing regulations regulated in the Omnibus Law. This research aims to determine the challenges and opportunities in licensing policy issues in the tourism sector that need reconstruction. The research method applied is normative legal research with a statutory and conceptual approach. The Omnibus Law is the prominent rule that be analyzed. Meanwhile, the concepts of licensing, authority, and the principle of community participation are used as the basis for analyzing and reconstructing regulations. The results of this research show that there are challenges in reconstructing licensing regulations in the Omnibus Law due to differences in perspectives on licensing concepts between the central government and regional governments, which have implications for shifting the objectives of issuing permits and the transfer of authority to issue licenses that the regional government initially owned created chaos in the supervision of tourism business activities. Still, the opportunity in this policy reconstruction is that it is still possible to revise laws based on the principle of real participation with community involvement mechanisms that can influence the final results of policy decisions, as well as active collaboration between governments at the central, regional and regional levels, stakeholders and the community in developing the tourism sector which can realize social welfare.